The ball search field task in the evaluation of methylphenidate treatment of children with attention deficit / hyperactivity disorder. (November 2020) - Rosetti, Marcos F.; Ulloa, Elena; Mayer, Pablo; Palacios-Cruz, Lino; de la Peña, Francisco R.; Hudson, Robyn
Highlights: Use of an ecologically relevant task to detect behavioral change following treatment. Participants in all conditions improved on retesting after two weeks. Controls significantly outperformed children with ADHD on a 1st and a 2nd evaluation. No clear effect following the administration of methylphenidate was found. Abstract: Assessing behavioral change in psychiatric contexts requires retesting patients where, however, ecologically relevant tasks are rarely used. We employed the Ball Search Field Task (BSFT) to evaluate the performance of attention deficit/hyperactivity disorder (ADHD) outpatients before and after administration of methylphenidate (MPH) and compared their performance with that of non-medicated ADHD outpatients and age-matched controls. The outpatient groups showed poorer performance at initial testing, improved performance at re-test although not to the level of the controls, and no clear effect of MPH treatment. The BSFT is thus sufficiently motivating and discriminating for the behavioral evaluation of treatments in psychiatric contexts.